Real-time observation of dynamic instability and adiabatic shear banding in pure titanium - Jianguo Li; Jingui Zhong; Longkang Li; Jiaming Han; Haosen Chen; Qiuming Wei; Tao Suo (Communications Materials)
Abstract Instability of various forms is a common phenomenon in condensed matter. The adiabatic shear bands (ASBs) of visco-plastic materials attract substantial attention in both academia and industry due to their critical impact on component safety, particularly under extreme impact loading conditions. Its occurrence on an extremely small temporal and spatial scale makes prediction extremely challenging. Here, we developed an advanced in-situ testing system to capture the onset of instability and real-time evolution of deformation and temperature fields. We reported an anisotropic instability behavior in pure Ti with two distinct ASB development modes under dynamic compression in different directions. In one case, no significant temperature rise was detected until ASB propagation began; in the other, thermal softening significantly affected dynamic instability. This anisotropy is likely due to differences in dominant plasticity mechanisms. More critically, detailed experiments revealed that microstructural evolution and microscale damage are key drivers of localized plastic instability.